Penerapan Movement dan Blocking dalam Membangun Dramatik melalui Pendekatan Director as Actor pada Film Lah, Kok Saya? - Lily Yunita Putri; Vicia Dwi Prakarti DB (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Lah, Kok Saya? is a short fiction film in the comedy-horror genre that portrays the dynamics of friendship among university students living in a boarding house, where a simple misunderstanding develops into a larger conflict. This creative work aims to apply movement and blocking to build dramatic elements through the director as actor approach. The creation process was carried out through pre-production, production, and post-production stages, utilizing the acting methods of Emotional Triggering, Physical Mimicry, and Line Feeding to help actors understand their characters and emotional motivations. The application of movement and blocking was focused on nine key scenes with high dramatic intensity. The results show that the director as actor approach effectively supported dramatic development through the arrangement of movement and blocking, with seven out of nine analyzed scenes successfully representing the intended emotions and conflicts, while two scenes were not fully achieved due to limitations in actor immersion, improvisation, and shot variation. Overall, the director as actor approach proved effective in supporting the direction of Lah, Kok Saya? through the application of movement and blocking to enhance dramatic impact.